Willingness-to-pay for hazard safety – A case study on the valuation of flood risk reduction in Germany. (August 2020) - Entorf, Horst; Jensen, Anne
Highlights: New survey on the willingness-to-pay (WTP) for the reduction of natural hazard risks in Germany. Annual median WTP amounts to 50 €; average WTP is sensitive to outliers. Main drivers of WTP: prior flood experience, family income, property situation, and age. The WTP-age profile is convex; WTP is relatively high for young and senior residents. Abstract: This paper focuses on the willingness-to-pay (WTP) for public investments in safety measures, in particular for reducing the risk of natural flood hazard. The study uses the method of contingent valuation to collect individual data from a nationwide sample of German households. Regarding the absolute value of estimated WTP, our results reveal that average values are sensitive to outliers and median values should be preferred. The median annual WTP turns out to be 50 €. A multivariate analysis of the determinants of WTP shows that prior experience with flooding is of key importance. We further conclude that the true ability to pay is highly significant for the stated willingness-to-pay. The multivariate approach also sheds some light on the complex relationship between age and WTP. We find a convex link between WTP and age. It might stem from a higher awareness of environmental problems among the younger generation, and from higher risk aversion among the elderly. We conclude that governmental safety policy initiatives could be fruitful in protection against flood risks in Germany. However, we also observe that better knowledge of climate risks would strongly improve the willingness of the German population to invest in safety measures.